An electronic clinical decision support system for the assessment and management of suicidality in primary care - Horrocks, Matthew; Michail, Maria; Aubeeluck, Aimee; Wright, Nicola; Morriss, Richard (JMIR Publications, 2018)
Background: Suicide is a global public health concern, but it is preventable. Increased contact with primary care before the suicide or attempted suicide raises opportunities for intervention and prevention. However, suicide assessment and management is an area that many General Practitioners (GPs) find particularly challenging. Previous research has indicated significant variability in how GPs understand, operationalise and assess suicide risk which subsequently has an impact on clinical decision making. Clinical Decision Support systems (CDSS) have been widely implemented across different healthcare settings, including primary care to support practitioners in clinical decision making. CDSS may reduce inconsistencies in the identification, assessment and management of suicide risk by GPs by guiding them through the consultation and generating a risk assessment plan that can be shared with a service user or with specialised mental health services. Objective: To co-develop and test with end users (e.g. GPs, primary care attendees, mental health professionals) an e-CDSS to support GPs in the identification, assessment and management of suicidality in primary care. Methods: An ongoing embedded mixed methods study with four phases: 1) Qualitative interviews with GPs to explore their views on the content, format and use of the e-CDSS; consultation with two service user advisory groups (people aged ≤ 25 and people aged ≥25) to inform the content of the e-CDSS including phrasing of items and clarity; 2) Participatory co-production workshops with GPs, service users and clinical experts in suicidality to determine the content and format of the e-CDDS; gain consensus of the relevance of items; establish content validity (CVI) and identify pathways to implementation, using the Consolidated Framework for Implementation Research; 3) Building the e-CDSS so that it guides the GP through a consultation and 4) Usability testing of the e-CDSS with GPs and service users in one primary care practice involving a non-live and a live stage. Conclusions: This study will be the first to explore the feasibility, acceptability and usability of electronic guided decision support system for use in primary care consultations for the improved assessment and management of suicidality.